Effect of the amount of ethanol on the melting temperature of palm oil fractions - Петік, Павло Федорович; Папченко, Вікторія Юріївна; Демидов, Ігор Миколайович; Кузнецова, Лариса Миколаївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the fractionation process of the palm oil by crystallization from a solution in the organic solvent - ethanol, in order to obtain the fractions of palm oil, which are used for the production of margarine, milk fat replacers, cocoa butter, confectionery and cooking fats, soaps. As the objects of study of fractionation the palm oil was chosen because it contains a significant proportion of 2-oleodysaturated triacylglycerols, the bulk of which is presented by 2-oleodipalmitin, which is the most promising raw material for the production of cocoa butter substitutes. The study suggested the use of ethanol because it is a food substance unlike acetone and hexane. The presence of the solvent gives the possibility to achieve higher speed of crystallization, to obtain fractions with a narrow range of characteristics, to obtain the mid fraction of the palm oil. It also improves the efficiency of separation of solid and liquid fractions at the filtration stage. The effect of ethanol on the yield and melting temperature of fractions of the palm oil was studied.